Orphan train ebook A novel. - Kline, Christina Baker (2013)
The #1 New York Times Bestseller Now featuring a sneak peek at Christina's forthcoming novel The Exiles, coming August 2020. "A lovely novel about the search for family that also happens to illuminate a fascinating and forgotten chapter of America's history. Beautiful."—Ann Packer Between 1854 and 1929, so-called orphan trains ran regularly from the cities of the East Coast to the farmlands of the Midwest, carrying thousands of abandoned children whose fates would be determined by pure luck. Would they be adopted by a kind and loving family, or would they face a childhood and adolescence of hard labor and servitude? As a young Irish immigrant, Vivian Daly was one such child, sent by rail from New York City to an uncertain future a world away. Returning east later in life, Vivian leads a quiet, peaceful existence on the coast of Maine, the memories of her upbringing rendered a hazy blur. But in her attic, hidden in trunks, are vestiges of a turbulent past. Seventeen-year-old Molly Ayer knows that a community service position helping an elderly woman clean out her home is the only thing keeping her out of juvenile hall. But as Molly helps Vivian sort through her keepsakes and possessions, she discovers that she and Vivian aren't as different as they appear. A Penobscot Indian who has spent her youth in and out of foster homes, Molly is also an outsider being raised by strangers, and she, too, has unanswered questions about the past. Moving between contemporary Maine and Depression-era Minnesota, Orphan Train is a powerful novel of upheaval and resilience, of second chances, and unexpected friendship.